ProMoX: A protocol stack monitoring framework - Weingärtner, Elias; Terwelp, Christoph; Wehrle, Klaus (Electronic Communications of the EASST, 2009)
In this paper, we present a preliminary glance on our framework for protocol stack monitoring using Xen (ProMoX). ProMoX uses the Xen hypervisor to virtualize entire instances of operating systems which may execute any arbitrary protocol implementation. By utilizing system virtualization for external monitoring, ProMoX can transparently inspect any protocol state and performance metrics of protocol implementations carried by a guest operating system. This way, ProMoX supports both the indentification of faults within early prototypes as well as the evaluation of new protocol designs.